Primary study of plastic micro fibre waste for sound absorption applications - Astrauskas, Tomas; Pranskevičius, Mantas; Januševičius, Tomas (International Conference “Environmental Engineering”, 2023)
Plastic and waste production has increased significantly in recent years. According to the various predictions the plastic production is not slowing down in the near future. Since 1960, plastic production has risen to 322 million tonnes in 2015 and expected to double in the next 20 years (Lusher et al., 2017). According to the 2020 statistical data, the leading sectors in plastic demand are packaging, building and construction, with 40.5% and 20.4% respectively. In 2019, an estimated 41% of plastic packaging waste was recycled in the EU. Despite the advantages of plastic recycling technologies, there are also a number of problems. Mechanical recycling refers to the processing of plastics waste into secondary raw material or products without significantly changing the material’s chemical structure. In this paper, we focused at the problem of plastic micro fibre (PMF) waste, which generated during mechanical recycling. The possibilities of using PMF for sound absorption applications are tested. For primary acoustic characterisation PMF was not treated thermally or bound using other materials. The controlled parameter of the material is density. The density of material changed from 100 to 300 kg/m3. The PMF sound absorption characterisation was performed using standard transfer function method (ISO 10534-2). The acoustic performance of materials predicted with acoustic porous materials Delany-Bazley-Miki model. The aim of this paper is to gain the essential knowledge about the plastic micro fibre sound absorption performance to find the possible recycling application for sound absorption.
Keywords: sound absorption; waste; plastic micro fibres; density; air flow resistivity